Kedudukan hukum atas Tanah Grondkaart sebagai bukti penguasaan tanah dalam Hukum Positif di Indonesia - Agra Hayyudya Arika, Cindy; Masykur, Hamidi; Supriyadi , Bambang Eko (Faculty of Law, Universitas Pekalongan, 2024)
Land ownership must be followed by evidence, so in this case the urgency of proving ownership of land rights is essential, so that it must produce products that have legal certainty of ownership of land. However, proving land ownership has always invited polemics, especially the legacy of railroad assets during the Dutch colonial era in the form of a map, namely